2021
DOI: 10.1186/s13638-021-01908-4
|View full text |Cite
|
Sign up to set email alerts
|

Optimization algorithm and simulation of supply chain coordination based on cross-border E-commerce network platform

Abstract: With the rapid development of cross-border e-commerce, the improvement of consumer satisfaction has become the focus of cross-border e-commerce platform optimization. Relying on advanced algorithm technology, it can realize the accurate and efficient matching between massive information and users, which is conducive to improving the user experience. Based on the consideration of consumer satisfaction, this paper constructs a dual channel supply chain composed of cross-border suppliers, cross-border e-commerce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…Enterprises dealing with the e-commerce are in good position to use social influence among customers as a tool to help in the course of decision-making by enabling the customer to claim suitability guidelines and reviews 20 . In a research 21 from 2021 is indicated that companies that deals with the e-commerce can through the online channels make an agreement about forming the revenues to optimize decentralized decision-making and to achieve significant cooperation between supply chain participants. When implementing e-commerce, the main problem is the structure of software components and arising of possible, potential integration shortcomings that are often overlooked through the logic of a business application.…”
Section: The Meaning Of E-commercementioning
confidence: 99%
“…Enterprises dealing with the e-commerce are in good position to use social influence among customers as a tool to help in the course of decision-making by enabling the customer to claim suitability guidelines and reviews 20 . In a research 21 from 2021 is indicated that companies that deals with the e-commerce can through the online channels make an agreement about forming the revenues to optimize decentralized decision-making and to achieve significant cooperation between supply chain participants. When implementing e-commerce, the main problem is the structure of software components and arising of possible, potential integration shortcomings that are often overlooked through the logic of a business application.…”
Section: The Meaning Of E-commercementioning
confidence: 99%
“…Supply chain financing refers to providing financial support and services to different participants in the entire supply chain through financial instruments to meet the financial needs of their production and trading activities. This form of financing not only covers the enterprise's own financing needs but also focuses on the upstream and downstream partners of the supply chain [1,2] and realizes the flexible management of capital flow through financial tools. Its advantages speak for themselves.…”
Section: Introductionmentioning
confidence: 99%
“…In the current context, cross-border ecommerce, with its innovative trade methods, provides unique opportunities and challenges for optimizing global energy trade [3] . The rapid rise of e-commerce has brought about digital and intelligent changes in various industries, and in the energy sector, this trend offers unprecedented opportunities to break through traditional trade barriers and promote international cooperation and development [4] . Cross-border e-commerce is driven by its ability to improve trade efficiency, reduce transaction costs, and drive the evolution of the energy market toward a more innovative, more efficient, and sustainable direction.…”
mentioning
confidence: 99%